2003
DOI: 10.1590/s0034-89102003000300002
|View full text |Cite
|
Sign up to set email alerts
|

Abundância de culicídeos em área metropolitana preservada e suas implicações epidemiológicas

Abstract: The most frequent and abundant species have been implicated in disease transmission to man in other regions. Attention must be given to these Culicidae since the study area is located near to an urban center, which could amplify the conditions for spreading vector diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 12 publications
2
19
0
16
Order By: Relevance
“…Essa espécie é antropofílica e capaz de viver em ambientes naturais, rurais ou até urbanos (Forattini et al 1981, 1995, Guimarães et al 2000, Taipe-Lagos & Natal 2003. Está amplamente distribuída no Brasil e em outros países da Região Neotropical (Forattini 2002) e possui importância para a saúde pública devido a sua competência vetora para arbovírus e filárias patogênicas (Rachou et al 1955, Forattini et al 1995, Macedo et al 1998, Lima & Ahid 2004.…”
Section: Introductionunclassified
“…Essa espécie é antropofílica e capaz de viver em ambientes naturais, rurais ou até urbanos (Forattini et al 1981, 1995, Guimarães et al 2000, Taipe-Lagos & Natal 2003. Está amplamente distribuída no Brasil e em outros países da Região Neotropical (Forattini 2002) e possui importância para a saúde pública devido a sua competência vetora para arbovírus e filárias patogênicas (Rachou et al 1955, Forattini et al 1995, Macedo et al 1998, Lima & Ahid 2004.…”
Section: Introductionunclassified
“…Although various studies have already been carried out in fragments of green areas inside urban Sã o Paulo, the data accumulated from these studies are not comprehensive enough to allow us to claim that all the Culicidae fauna in these areas are known (Urbinatti et al 2001, Taipe-Lagos & Natal 2003, Montes 2005. Comparison of the findings of a preliminary study (Medeiros-Sousa et al 2013) of Carmo Park and Chico Mendes Park with the data from the present study, which found nineteen taxons in Carmo Park, shows that eleven of these taxons had already been recorded and that eight were found here for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Em 2006, o vírus foi isolado em duas províncias na Argentina. Com a proximidade entre o Brasil e a Argentina, a possibilidade da introdução do vírus em território brasileiro deve ser vista com cautela [9][10][11] .…”
Section: Discussionunclassified